Valuation of innovation: the case of iPhone - Timo Korkeamäki; Tuomas Takalo (Bank of Finland, 2012)
We study the value of innovation in a case study of one of the most visible innovative products in recent years, Apple s iPhone. The value effects of news announcements, patent publications, and trademarks relating to iPhone are taken into account. Our estimate of the lower bound on the value of iPhone is fairly high, 30 billion U.S. (event-day) dollars or 10% to 13% of the firm s market cap (at the end of 2009). We find that patentable technology explains about 25% of the total value, which derives from market reactions to publication of patent applications rather than grants. We also observe a weak negative reaction among Apple s rivals to news about iPhone. Apple appears to capture most of the value within the iPhone supply chain.
URN:NBN:fi:bof-20140807657
Keywords: 330